HAMBATAN BERLAKUNYA UNDANG UNDANG NOMOR 19 TAHUN 2002 TENTANG HAK CIPTA - ANGGO DOYOHARJO (Universitas Slamet Riyadi, 2010)
AbstractThe Copy-right Act is a modern law/regulation and it is not rooted from any culture in Indonesia. Yet, as a positive law, it has the power to regulate and to enforce people. The impediment of The Copy-right Act practices are caused by the lack of information on copy-right law in Indonesia. Consequently, there are lack awareness of people to obey the Copy-right law. Keywords: impediment, copy-right practices.